2018
DOI: 10.1002/pbc.27457
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and nature of hearing loss in a cohort of children with sickle cell disease

Abstract: Background: Sickle cell disease (SCD) may cause injury to any organ, including the auditory system. Although the association of SCD and hearing loss has been described, the nature of this complication is unknown. We sought to establish the prevalence and nature of hearing loss in a referred cohort of children with SCD and to identify correlating disease-or treatment-associated factors. Procedure:We conducted a retrospective review of patients with SCD < 22 years of age who had hearing evaluations between Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
2
11
0
1
Order By: Relevance
“…Through this systematic review and meta‐analysis of population‐based prevalence studies, we observed an SNHL prevalence of 20.5% among in SCA patients, indicating a significantly higher prevalence in SCA patients than in healthy controls (HC) (0–7.5%) despite the variability between the studies.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Through this systematic review and meta‐analysis of population‐based prevalence studies, we observed an SNHL prevalence of 20.5% among in SCA patients, indicating a significantly higher prevalence in SCA patients than in healthy controls (HC) (0–7.5%) despite the variability between the studies.…”
Section: Discussionmentioning
confidence: 86%
“…Of these 27 studies, six were excluded because they did not differentiate between homozygotes (SCA) and heterozygotes in the methods and/or in the results. Thus, 21 articles were included in this systematic review (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations